INNOVATIVE DEVELOPMENT AND ECOLOGICAL EFFICIENCY: INTERNATIONAL APPROACHES TO EVALUATING ENTERPRISE ACTIVITIES - Yuldasheva, Nazokat (International Conference on Business & Management, 2026)
The growing global transition toward sustainable development has significantly increased the importance of integrating innovative development with ecological efficiency in enterprise management and evaluation systems. This study examines international approaches to assessing enterprise activities at the intersection of innovation performance and environmental sustainability. The research analyzes the evolution of theoretical perspectives on green innovation, from the traditional view of environmental responsibility as an additional economic burden to contemporary concepts emphasizing the potential compatibility of ecological efficiency and competitive advantage.